The Beginning of Lay Teachers' Training in Lithuania - Minginas, Jonas (Acta Paedagogica Vilnensia, 2000)
The aim of article is to investigate the experience of training primary school lay teachers in 1773-1759.
Keywords: Society of Jesus; Ignacy Jakub Massalski; Commission of National Education; teachers' Seminary.